Readability and Understandability Scores for Snippet Assessment: an Exploratory Study - Dantas, Carlos Eduardo C.; Maia, Marcelo A. (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2021: Anais do IX Workshop de Visualização, Evolução e Manutenção de Software, 2021)
Code search engines usually use readability feature to rank code snippets. There are several metrics to calculate this feature, but developers may have different perceptions about readability. Correlation between readability and understandability features has already been proposed, i.e., developers need to read and comprehend the code snippet syntax, but also understand the semantics. This work investigate scores for understandability and readability features, under the perspective of the possible subjective perception of code snippet comprehension. We find that code snippets with higher readability score has better comprehension than lower ones. The understandability score presents better comprehension in specific situations, e.g. nested loops or if-else chains. The developers also mentioned writability aspects as the principal characteristic to evaluate code snippets comprehension. These results provide insights for future works in code comprehension score optimization.